PCR-based construction and transformation of CodY gene deletion construct in Streptococcus pneumoniae - Mohamed Rehan, Aisyah; Enche Othman, Mohamad Izwan; Mohd Amin, Nor Munirah; Shahdan, Intan Azura; Ahmad Yusof @ Hanafi, Hanani (2017)
Introduction: Streptococcus pneumoniae (S. pneumoniae) is a gram-positive diplococci belonging to the genus Streptococcus and it is a well-studied pathogenic bacterium. Pneumococcal diseases such as otitis media, pneumonia, sepsis and meningitis caused by pathogenic strains of S. pneumoniae still brought significant mortality and morbidity rate worldwide. The pathogenicity of S. pneumoniae is exerted by various virulence factors and one of it is the enzyme hyaluronate lyase. Hyaluronate lyase plays major role in invasive capability of S. pneumoniae. Its mechanism of action and crystallographic structure has been determined but its regulatory mechanism is still poorly understood. Drawing connections between nutritional behaviours and invasive property of S. pneumoniae, CodY regulator is hypothesized as a potential hyaluronate lyase regulator. This work is aimed to construct CodY deficient mutant of S. pneumoniae to form foundational work for the study of CodY regulatory effect on hyaluronate lyase. Materials and method: A single gene-deletion method was chosen to create CodY mutant construct containing aphA-3 gene (encoding kanamycin resistance protein) replacement cassette by employing recombinant fusion PCR method. A single band DNA product at the expected size of 2,563 bp after recombinant fusion PCR was visualized on agarose gel electrophoresis. This indicates a high probability that the linear recombinant amplicon has been successfully constructed. The recombinant amplicon was transformed into S. pneumoniae cells of Malaysian local clinical isolate by employing the competence stimulating peptide (CSP-1) to enhance and induce natural competence. Results: No viable CodY mutant was evident post-transformation. The negative transformation results are postulated to be due to the essential nature of CodY regulator. Conclusion: This work can provide basis for recombinant fusion PCR method in designing and constructing single gene deletion construct. However, further works are needed to identify the regulatory agent of hyaluronate lyase.